A Cell Proliferation and Inflammatory Signature Is Induced by Lawsonia intracellularis Infection in Swine - Fernando L. Leite (American Society for Microbiology, 2019)
ABSTRACT Lawsonia intracellularis causes porcine proliferative enteropathy. This is an enteric disease characterized by thickening of the wall of the ileum that leads to decreased growth of animals and diarrhea. In this study, we investigated the host response to L. intracellularis infection by performing transcriptomic and pathway analysis of intestinal tissue samples from groups of infected and noninfected animals at 14, 21, and 28 days postchallenge. At the peak of infection, when animals developed the most severe lesions, infected animals had higher levels of several gene transcripts involved in cellular proliferation and inflammation, including matrix metalloproteinase-7 (MMP7), transglutaminase-2 (TGM2), and oncostatin M (OSM). Histomorphology also revealed general features of intestinal inflammation. This study identified important pathways associated with the host response in developing and resolving lesions due to L. intracellularis infection. IMPORTANCE Lawsonia intracellularis is among the most important enteric pathogens of swine, and it can also infect other mammalian species. Much is still unknown regarding its pathogenesis and the host response, especially at the site of infection. In this study, we uncovered several novel genes and pathways associated with infection. Differentially expressed transcripts, in addition to histological changes in infected tissue, revealed striking similarities between L. intracellularis infection and cellular proliferation mechanisms described in some cancers and inflammatory diseases of the gastrointestinal tract. This research sheds important light into the pathogenesis of L. intracellularis and the host response associated with the lesions caused by infection.